Efficacy and Safety of Endoscopic Balloon Dilatation for Treatment of Primary Obstruction Megaurater Up to 2 Years of Age - Tariq Ahmad, Sher Wali Khan, Muhammad Javed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Endoscopic balloon dilatation (EBD) can be performed with different catheters and its durability is still controversial. The study aimed to compare long-term results of EBD performed <20 months of age using balloons of 4 mm vs. 6 mm in diameter. Retrospective study conducted of consecutive patients with unilateral primary obstructive megaureter (POM) undergoing EBD <24 months of age by two surgeons from January 2020 to January 2022. The technique was consistent, but for balloon diameter was 5 mm in group A vs. 6 mm in group B. End-points included peri-operative complications, success rate (improving dilatation and non-obstructive drainage on 9-month scintigraphy), and long-term outcome (need for reimplantation and diameter of retrovesical ureter at last ultrasound). The procedure was completed in all planned patient. Group A included 30 patients and Group B 60 patients. Groups were not significantly different for age (p < 0.09), gender (p < 0.1), laterality (p < 0.7), and preoperative median ureteral diameter (p Z 0.08). No perioperative complications occurred. Four group A patients required a cutting balloon to achieve a satisfactory dilatation of the vesicoureteral junction (p Z 0.009). After a median (range) follow-up of 70 (19e155) months, success rate was 73.3% vs. 83.3% (p Z 0.45), 4/15 group A and 5/30 group B patients required reimplantation within 2 years of EBD. In successful cases, median (range) ureteral diameter at last follow-up was 6 (0-17) mm vs. 5 (0-16) mm, which was significantly better than preoperative value (p Z 0.003 and p < 0.001, respectively), but not significantly different (p Z 0.8) between groups. EBD is an umbrella term that encompasses many technical variations, which can be key for success. Although limited by the small numbers and the comparison of patients treated over two subsequent periods, this is the first study focusing on the role of balloon size. The diameter of the balloon did not influence significantly long-term results, but the 6 mm balloon slightly increased the success rate of EBD to 83.3% and eliminated the need for cutting balloons to achieve a satisfactory dilatation.